A critical analysis of L-asparaginase activity quantification methods—colorimetric methods versus high-performance liquid chromatography - Magri, Agnes [UNESP]; Soler, Matheus F. [UNESP]; Lopes, André M. [UNESP]; Cilli, Eduardo M. [UNESP]; Barber, Patrick S.; Pessoa, Adalberto; Pereira, Jorge F. B. [UNESP] (Springer Nature, 2018)
L-asparaginase or ASNase (L-asparagine aminohydrolase, E.C.3.5.1.1) is an enzyme clinically accepted as an antitumor agent to treat acute lymphoblastic leukemia (ALL) and lymphosarcoma through the depletion of L-asparagine (L-Asn) resulting in cytotoxicity to leukemic cells. ASNase is also important in the food industry, preventing acrylamide formation in processed foods. Several quantification techniques have been developed and used for the measurement of the ASNase activity, but standard pharmaceutical quality control methods were hardly reported, and in general, no official quality control guidelines were defined. To overcome this lack of information and to demonstrate the advantages and limitations, this work properly compares the traditional colorimetric methods (Nessler; L-aspartic acid β-hydroxamate (AHA); and indooxine) and the high-performance liquid chromatography (HPLC) method. A comparison of the methods using pure ASNase shows that the colorimetric methods both overestimate (Nessler) and underestimate (AHA and indooxine) the ASNase activity when compared to the values obtained with HPLC, considered the most precise method as this method monitors both substrate consumption and product formation, allowing for overall mass-balance. Correlation and critical analysis of each method relative to the HPLC method were carried out, resulting in a demonstration that it is crucial to select a proper method for the quantification of ASNase activity, allowing bioequivalence studies and individualized monitoring of different ASNase preparations. [Figure not available: see fulltext.]
Keywords: Enzymatic activity; Indooxine; L-asparaginase; L-aspartic acid; L-aspartic acid β-hydroxamate; Nessler